The Influence of Pancasila Education Learning on the Formation of Nationalism Character of Grade IX Students at UPT SMP Negeri 5 Tambang - Aprillia, Delvi; Primahardani, Sri Erlinda Indra (Journal of Educational Sciences, 2025)
This study is motivated by the low level of nationalism among students, reflected in their limited awareness of preserving local culture, lack of willingness to make sacrifices, low appreciation for the services of national heroes, tendency to prioritize personal interests over public interests, as well as a weak sense of patriotism and pride as Indonesian citizens. The aim of this study is to determine whether Pancasila Education has an effect on shaping the nationalist character of ninth-grade students at UPT SMP Negeri 5 Tambang. This research uses a descriptive quantitative approach, with data collection methods consisting of questionnaires and interviews. The data analysis results indicate a positive and significant effect of Pancasila Education on the development of students’ nationalist character. This is evidenced by a calculated F-value of 28.395 ≥ F-table 4.04 and a significance value of 0.000 ≤ 0.05. Therefore, Ho is rejected and Ha is accepted, indicating a significant simultaneous effect. The coefficient of determination analysis shows that 37.2% of the formation of nationalist character is influenced by Pancasila Education, while 62.8% is affected by other factors beyond the scope of this study.